The Elusive Discretionary Function Exception from Government Tort Liability: The Narrowing Scope of Federal Liability - Bagby, John W.; Gittings, Gary L. (American Business Law Journal, 1992)
Disclaimer: This summary was generated by AI based on the content of the source document.